Exploring the Awareness and Counseling Practices of Community Pharmacists in Libya Regarding Drug Interactions with Oral Hypoglycemic Medications - Rghebi, Nabila; Alsbani, Ensherah Ben Zekri (AlQalam Journal of Medical and Applied Sciences, 2024)
The increasing prevalence of polypharmacy increases the patient's risk of drug side effects and drug interactions, especially among patients with type 2 diabetes. Pharmacists are essential to provide effective education and counseling to these patients. This study aims to assess the awareness and counseling practice of community pharmacists in Libyan regarding potential drug interactions involving oral hypoglycemic agents in patients with type 2 diabetes. A cross-sectional descriptive study was adapted in 2020 in Tripoli, Libya, and included a questionnaire distributed to 150 community pharmacists. The majority of pharmacists (79%) had a bachelor’s degree, and (45%) of them had (2-4) years of experience. The vast majority (94%) of participants were familiar with the term drug interactions and counseling guidelines for patients with diabetes. (65%) of pharmacists advised diabetic patients on the appropriate times to check blood sugar levels. (84%) were aware of drugs that interact with oral hypoglycemic drugs. (60%) advised patients to visit their physician if a patient came to their community pharmacy to be dispensed sitagliptin and captopril, to avoid drug interactions with oral hypoglycemic drugs. The study revealed that the majority of Libyan pharmacists in community pharmacies were aware of the term drug interactions and advised diabetic patients, were aware of drugs that interact with oral hypoglycemic drugs. إن الانتشار المتزايد لتعدد الأدوية يزيد من خطر تعرض المريض للآثار الجانبية للأدوية والتفاعلات الدوائية، وخاصة بين مرضى السكري من النوع 2. والصيادلة ضروريون لتوفير التعليم والإرشاد الفعال لهؤلاء المرضى. تهدف هذه الدراسة إلى تقييم ممارسات التوعية والإرشاد لدى صيادلة المجتمع في ليبيا فيما يتعلق بالتفاعلات الدوائية المحتملة التي تنطوي على أدوية خفض سكر الدم عن طريق الفم لدى مرضى السكري من النوع 2. تم تكييف دراسة وصفية مقطعية في عام 2020 في طرابلس، ليبيا، وتضمنت استبيانًا تم توزيعه على 150 صيدلي مجتمع. كان لدى غالبية الصيادلة (79٪) درجة البكالوريوس، وكان لدى (45٪) منهم (2-4) سنوات خبرة. كانت الغالبية العظمى (94%) من المشاركين على دراية بمصطلح التفاعلات الدوائية وإرشادات مرض السكري، ونصح (65%) من الصيادلة مرضى السكري بالأوقات المناسبة لفحص مستويات السكر في الدم، وكان (84%) على دراية بالأدوية التي تتفاعل مع أدوية خفض السكر عن طريق الفم. ونصح (60%) المرضى بزيارة طبيبهم إذا جاء مريض إلى صيدليتهم المجتمعية لصرف سيتاجليبتين وكابتوبريل، لتجنب التفاعلات الدوائية مع أدوية خفض السكر عن طريق الفم. كشفت الدراسة أن غالبية الصيادلة في الصيدليات المجتمعية كانوا على دراية بمصطلح التفاعلات الدوائية ونصحوا مرضى السكري، وكانوا على دراية بالأدوية التي تتفاعل مع أدوية خفض السكر عن طريق الفم